THE MODELING OF GRAPHICAL AND ANALYTICAL DRYING PROCESS PARAMETERS RELATIONS IN CO2 ENVIRONMENT - NATALIA TISLINSCAIA (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2017)
The engineering calculation of such dryer could be approximately done using Id-diagrams. There is such a diagram for air based dryers graphical and analytical calculation. The use of this diagram for CO2 modified environment is impossible; because it shows the thermo-physical characteristics for air which significantly differs from those of CO2. We made a tentative of modeling and calculate all the necessary parameters based on which there was created an Id-diagram for CO2 modified environment. Obtained graphical relations for temperature, enthalpy, moisture content and partial pressure will allow one to use them for CO2 modified environment based dryers.